Search for neutrino emission from cores of active galactic nuclei - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alispach, C.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; et al. (Physical Review D, 2022)
The sources of the majority of the high-energy astrophysical neutrinos observed with the IceCube neutrino telescope at the South Pole are unknown. So far, only a flaring gamma-ray blazar was compellingly associated with the emission of high-energy neutrinos. However, several studies suggest that the neutrino emission from the gamma-ray blazar population only accounts for a small fraction of the total astrophysical neutrino flux. In this work we probe the production of high-energy neutrinos in the cores of active galactic nuclei (AGN), induced by accelerated cosmic rays in the accretion disk region. We present a likelihood analysis based on eight years of IceCube data, searching for a cumulative neutrino signal from three AGN samples created for this work. The neutrino emission is assumed to be proportional to the accretion disk luminosity estimated from the soft x-ray flux. Next to the observed soft x-ray flux, the objects for the three samples have been selected based on their radio emission and infrared color properties. For the largest sample in this search, an excess of high-energy neutrino events with respect to an isotropic background of atmospheric and astrophysical neutrinos is found, corresponding to a post-trial significance of 2.60σ. If interpreted as a genuine signal with the assumptions of a proportionality of x-ray and neutrino fluxes and a model for the subthreshold flux distribution, then this observation implies that at 100 TeV, 27%-100% of the observed neutrinos arise from particle acceleration in the core of AGN at 1σ confidence interval.